Pre-inflation: Origin of the Universe from a topological phase transition - Bellini, Mauricio (2017)
I study a model which describes the birth of the universe using a global topological phase transition with a complex manifold where the time, τ, is considered as a complex variable. Before the big bang τ is a purely imaginary variable so that the space can be considered as Euclidean. The phase transition from a pre-inflation to inflation is examined by studying the dynamical rotation of the time on the complex plane. Back-reaction effects are exactly calculated using Relativistic Quantum Geometry.